Transient Hyperglycemia in Neonate: A Case Report - Banik, SK; Sarker, S; Islam, MZ; Nahar, N (Bangladesh Medical Journal, 2014)
Hyperglycemia has become a significant risk factor for morbidity and mortality as smaller and more fragile infants survive during the neonatal period. Historically, hyperglycemia has been attributed to excessive IV glucose infusion. More recent studies indicate that physiologic and biochemical mechanisms, leading to excess glucose production, insulin resistance, or glucose intolerance, underlie the development of hyperglycemia in preterm infants and sometimes inhibit efforts to maintain normal glycemia in the neonate. The sequelae of these disturbances in glucose metabolism are extensive. Efforts to prevent hyperglycemia should include general measures to improve the health of the infant and attempts to treat pathophysiologic conditions and diseases. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18810 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 54-56